Nonlinear Oxidation Behavior in Pure Ni and Ni-Containing Entropic Alloys - Xia, Songqin; Lousada, Cláudio M.; Mao, Huahai; Maier, Annika C.; Korzhavyi, Pavel A.; Sandström, Rolf; Wang, Yugang; Zhang, Yong (Frontiers in Materials, 2018)
We performed a combined experimental and theoretical investigation of the oxidation behavior of pure Ni and of the following multi-component Ni-containing alloys with nearly equiatomic compositions: FeNi, CoFeNi, CoCrFeNi, and CoCrFeMnNi. The materials were exposed to air at ambient pressure and at a temperature of 800°C for 150 minutes, their weight-gain due to oxidation was continuously monitored and the products of oxidation were subsequently characterized by XRD. The most common oxides formed have spinel or halite structure and the materials resistance to oxidation increases as: FeNi < CoFeNi < Ni < CoCrFeMnNi < CoCrFeNi. We found further that the oxidation-resistance of the materials does not correlate linearly with the number of elements present, instead the type of elements impacts significantly the materials susceptibility to oxidative damage. Cr is the element that imparted higher resistance to oxidation while Mn and Fe worsened the materials performance. In order to better understand the mechanisms of oxidation we employed thermodynamic equilibrium calculations and predicted the phase stability of oxides of the elements that are present in the materials, in different ranges of temperature, composition and oxygen activity. Additionally, we determined the phase compositions for the thermodynamically stable oxides at 800°C. The results from the thermodynamic modelling are in good agreement with the experimental finds. The alloys with low resistance to oxidation such as CoFeNi and FeNi, form the Fe3O4 spinel phase which tends to dominate the phase diagram for these materials. The presence of Cr increases the resistance to atomic rearrangement due to slow diffusion in the complex structure of Cr containing spinel phases. This causes the extremely high resistance to oxidation of the CoCrFeNi alloy. The presence of Mn in CoCrFeNi stabilizes the Mn3O4 spinel which reduces the oxidation-resistance of the alloys due to the high mobility of Mn.